Faktor yang Mempengaruhi Perkembangan Tubuh dan Emosi Anak Usia 4–6 Tahun - Chofia Salsabila, Naila; Sianturi, Risbon; Firli, Ai; Aini, Wardiatul (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to identify and analyze the factors influencing the physical and emotional development of children aged 4–6 years. It adopts a qualitative descriptive research design. The subjects are early childhood teachers and parents, while the object is the set of factors affecting children's physical and emotional growth. Data were collected through literature reviews, interviews, and observations, and analyzed thematically. The findings reveal that emotional development in early childhood is significantly influenced by an interplay of biological factors (genetics, hormones, temperament), psychosocial elements (parenting, communication, social relationships), and environmental conditions (home, school, and culture). Physical development, such as muscle growth and motor skills, also contributes to the formation of self-concept and emotional regulation. The study concludes that family, educators, and social environments must provide holistic support to ensure balanced physical and emotional development in young children